Can I be sued for that? Liability risk and the disclosure of clinically significant genetic research findings - McGuire, Amy L.; Knoppers, Bartha Maria; Zawati, Ma’n H.; Clayton, Ellen Wright (Genome Research, 2014)
Genomic researchers increasingly are faced with difficult decisions about whether, under what circumstances, and how to return research results and significant incidental findings to study participants. Many have argued that there is an ethical—maybe even a legal—obligation to disclose significant findings under some circumstances. At the international level, over the last decade there has begun to emerge a clear legal obligation to return significant findings discovered during the course of research. However, there is no explicit legal duty to disclose in the United States. This creates legal uncertainty that may lead to unmanaged variation in practice and poor quality care. This article discusses liability risks associated with the disclosure of significant research findings for investigators in the United States.
10.1101/gr.170514.113